The impact of government spending on the economic indicators of the State of Palestine - Kamal Mohamed Abu Amsha, Mohamed (Journal of Research in Finance and Accounting, 2026)
The study aimed to identify the impact of public spending on economic indicators (economic growth, total exports, unemployment, total capital formation) in the State of Palestine, between the year 2000 - to year 2018, and the researcher used the descriptive analytical approach in the study, and the relevant data were collected in the study from the Palestinian Monetary Authority, the study concluded that there is a positive and statistically significant effect of government spending on economic growth (GDP), exports, and gross capital formation (GCF), and that an increase of one dollar in government spending will lead to an increase of 3.751 in growth. Economically, a 1 increase in government expenditures will result in a 0.727 increase in exports, and a 1 increase in government spending will result in a 0.691 increase in total Gross capital formation (GCF)